2023
DOI: 10.3389/fnins.2022.1060172
|View full text |Cite
|
Sign up to set email alerts
|

Aging alters across-hemisphere cortical dynamics during binaural temporal processing

Abstract: Differences in the timing and intensity of sounds arriving at the two ears provide fundamental binaural cues that help us localize and segregate sounds in the environment. Neural encoding of these cues is commonly represented asymmetrically in the cortex with stronger activation in the hemisphere contralateral to the perceived spatial location. Although advancing age is known to degrade the perception of binaural cues, less is known about how the neural representation of such cues is impacted by age. Here, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…In another study, older adults showed reduced contralateral lateralization of processing during passive listening to noise bursts with different interaural time differences (ITD), although the overall responses were larger in older adults (Eddins et al, 2022 ). This reduction was more pronounced for right-leading stimuli suggesting a hemispheric difference in the reduction of contralaterality with aging.…”
Section: Functional Alterations—eeg and Meg Studiesmentioning
confidence: 99%
“…In another study, older adults showed reduced contralateral lateralization of processing during passive listening to noise bursts with different interaural time differences (ITD), although the overall responses were larger in older adults (Eddins et al, 2022 ). This reduction was more pronounced for right-leading stimuli suggesting a hemispheric difference in the reduction of contralaterality with aging.…”
Section: Functional Alterations—eeg and Meg Studiesmentioning
confidence: 99%